Overview of Microorganism Patterns Causing Pathological Fluor Albus at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Raden Ayu Kusuma Andini; Ferry Yusrizal; Azhari Rozali; Theodorus (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Fluor albus, also known as leucorrhoea, vaginal discharge, or leukorrhea, is the name given to fluids that are secreted from the genitals that are not blood. Pathological fluor albus can be caused by an infection in the lower genitalia or in areas that are more proximal. This study aimed to determine the pattern of microorganisms that cause pathological fluor albus at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This study was a descriptive observational study and used primary data from a direct examination of research subjects at the obstetrics and gynecology polyclinic of Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. A total of 63 research subjects participated in this study. Analysis of microorganism patterns was carried out univariately using SPSS software. Results: The majority of microorganisms that cause pathological fluor albus are Gardnerella vaginalis. Meanwhile, in non-pathological conditions of fluor albus, the majority of causative microorganisms are E. coli. Conclusion: Gardnerella vaginalis is the most common causative microorganism of pathological fluor albus disorders at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.